Posterior Fossa Venous Drainage - de Miquel, María Angeles (Frontiers in Neurology, 2021)
This paper aims to make simple the evaluation of the main veins related to the brainstem and cerebellum. Posterior fossa venous drainage is best understood in context with its three main collectors: superior: toward the Vein of Galen; posterior: toward the torcular complex; and anterior: toward the superior petrosal sinus. A fourth possible drainage path, often harder to distinguish, is directed toward the inferior petrosal sinus. Veins of these four systems are frequently connected to one another. Despite traditionally being considered less regular than its arterial disposition, posterior fossa venous anatomy follows specific patterns that are easy to identify. The three more representative veins of each venous confluent have been selected, to help in recognizing them angiographically. Since pial large veins are primarily located over the surface of the encephalon, most related anatomical structures can be confidently identified. This is of special interest when angiographic 2D or 3D studies are evaluated and provide fundamental assistance in locating precise structures. To better aid in understanding venous disposition, an overview of embryologic and fetal development is also discussed.